Regulation in New Natural Gas Markets : The Northern Ireland Experience - Lehmann, Peter (World Bank, Washington, DC, 2012)
So far gas market liberalization has generally occurred in mature markets-particularly where much of the pipeline system has already been laid, as in Argentina, Britain, and the United States. In these cases a competitive structure is appropriate. In new markets, however, it may be difficult to introduce a competitive regime from the outset, and a different approach and form of regulation, such as a period of exclusive licenses, may be needed. In 1997 the Northern Ireland authorities awarded Phoenix Natural Gas an exclusive license for a limited period to develop a new gas market from scratch in the greater Belfast area. This Note explains the rationale for a period of exclusivity and describes Northern Ireland's approach to gas market regulation.